Sensory Afferent Renal Nerve Activated Gαi2 Subunit Proteins Mediate the Natriuretic, Sympathoinhibitory and Normotensive Responses to Peripheral Sodium Challenges - Moreira, Jesse D.; Nist, Kayla M.; Carmichael, Casey Y.; Kuwabara, Jill T.; Wainford, Richard D. (Frontiers in Physiology, 2021)
We have previously reported that brain Gαi2 subunit proteins are required to maintain sodium homeostasis and are endogenously upregulated in the hypothalamic paraventricular nucleus (PVN) in response to increased dietary salt intake to maintain a salt resistant phenotype in rats. However, the origin of the signal that drives the endogenous activation and up-regulation of PVN Gαi2 subunit protein signal transduction pathways is unknown. By the central oligodeoxynucleotide (ODN) administration we show that the pressor responses to central acute administration and central infusion of sodium chloride occur independently of brain Gαi2 protein pathways. In response to an acute volume expansion, we demonstrate, via the use of selective afferent renal denervation (ADNX) and anteroventral third ventricle (AV3V) lesions, that the sensory afferent renal nerves, but not the sodium sensitive AV3V region, are mechanistically involved in Gαi2 protein mediated natriuresis to an acute volume expansion (peak natriuresis (µeq/min) sham AV3V: 43±4 vs. AV3V 454 vs. AV3V + Gαi2 ODN 25±4, p<0.05; sham ADNX: 43±4 vs. ADNX 236, AV3V + Gαi2 ODN 25±3 p<0.05). Furthermore, in response to chronically elevated dietary sodium intake, endogenous up-regulation of PVN specific Gαi2 proteins does not involve the AV3V region and is mediated by the sensory afferent renal nerves to counter the development of the salt sensitivity of blood pressure (MAP [mmHg] 4% NaCl; Sham ADNX 1244 vs. ADNX 1454, p<0.05; Sham AV3V 1254 vs AV3V 1215). Additionally, the development of the salt sensitivity of blood pressure following central ODN-mediated Gαi2 protein down-regulation occurs independently of the actions of the brain angiotensin II type 1 receptor. Collectively, our data suggest that in response to alterations in whole body sodium the peripheral sensory afferent renal nerves, but not the central AV3V sodium sensitive region, evoke the up-regulation and activation of PVN Gαi2 protein gated pathways to maintain a salt resistant phenotype. As such, both the sensory afferent renal nerves and PVN Gαi2 protein gated pathways, represent potential targets for the treatment of the salt sensitivity of blood pressure.